New media fine art education platform based on internet of things technology. Issue 3 (31st August 2021) - Feng, Ruixia; Li, Tinghua; Dong, Junliang
In order to solve the problems of poor real-time output performance, poor resource recall performance and high execution time cost of the new media art information platform, this paper proposes to build a new media art education platform based on Internet-of-Things (IoT) technology. Firstly, the overall framework of the IoT platform is designed and the functional modules are divided for optimisation. Secondly, the VXI bus (vmebus extension for instrumentation) technology is used to optimise the resource acquisition. The comparative experiments show that the new media art education platform in this paper has good resource recall performance, and provides a relatively high recall rate of resource retrieval, 21% and 14% higher than the other two methods respectively. The execution time cost increases with the increase of the amount of educational resources data, but the execution time cost of this method is obviously less than that of the other two methods.